Minimization Of Heavy Metals Migration From Landfill Leachate By Using Admixture Of Laterite Soil And Pressmud - Mohamad, Maheera (2014)
This study emphasizes on field investigation and laboratory experiments involving characterization of enhancing laterite soil as daily soil cover and their suitability as proposed daily soil cover at the specifics landfill site. In this study, the laterite soil samples were mixed with waste from sugar refinery process, pressmud at difference percentage of weight ratio (10%, 30% and 50%). The physicochemical properties of the laterite soil, pressmud and laterite soil-pressmud mixtures characterization as well as leaching test were carried out. The physicochemical and engineering properties involved compaction bebavior, permeability, cation exchange capacity (CEC), compressive stress test and its surface functional groups. The leaching test method included batcb equilibrium test and soil column test. The optimum value of water content in the soilpressmud mixtures was determined in the compaction test. It was found out that the higher pressmud content in the soil, the higber optimum water content value observed.